(untitled) (Bangladesh Heart Journal, 2022)
A large ascending Aortic pseudoaneurysm is a rare life threatening complication after off pump coronary artery bypass surgery. We herein describe such a case of massive ascending Aortic pseudoaneurysm, with impending rupture which was adherent to undersurface of sternum, was successfully treated by us at Square Hospitals Limited. Bangladesh Heart Journal 2022; 37(1): 72-76